Faktor Dominan yang Mempengaruhi Keputusan Pembelian Sepeda Motor Yamaha NMAX di Muara Bulian - Ahmad Fithoni (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS GRAHA KARYA MUARA BULIAN, 2021)
This study aims to determine the dominant factors that influence the purchase decision of a Yamaha NMAX motorcycle in Muara Bulian. Respondents in this study were consumers who bought Yamaha NMAX motorbikes in Muara Bulian District. The sampling technique used non-probability sampling was used by incidental sampling, namely the sampling technique based on chance, anyone who met the researcher can be used as a sample, with the number of a sample of 100 respondents using the Multiple Linear Regression analysis method assisted by the SPSS 21 (Statistics Product and Service Solution) application. The results of the study based on the results of tests and regressions show that the variable product quality is the dominant factor affecting consumers in making purchasing decisions, followed by design, while promotion has no significant effect in a positive direction on purchasing decisions for Yamaha NMAX motorbikes in Muara Bulian.